2022
DOI: 10.1002/cjoc.202200122
|View full text |Cite
|
Sign up to set email alerts
|

From Fluorescent Probes to the Theranostics Platform

Abstract: What is the most favorite and original chemistry developed in your research group?Development of new responsive fluorescent molecules and using them as tools to study physiological and pathological processes of specific biomolecules. How do you get into this specific field?My original major is inorganic chemistry. Influenced by Prof. Chunhui Huang (academician), I was interested in fluorescent materials. The flowery color of fluorescent material itself and its important applications in the field of biological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 133 publications
0
6
0
Order By: Relevance
“…In recent decades, fluorescence imaging has been widely used in biological research because of its advantages of simple operation and rapid real‐time analysis. [ 1‐4 ] It is crucial to explore fluorescence probes with high sensitivity, photostability, and biocompatibility for fluorescence imaging. In particular, fluorescent probes with near‐infrared (NIR) emission (> 650 nm) have great potential due to their advantages of low photodamage to organisms, high signal‐to‐noise ratio, and deep tissue penetration.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…In recent decades, fluorescence imaging has been widely used in biological research because of its advantages of simple operation and rapid real‐time analysis. [ 1‐4 ] It is crucial to explore fluorescence probes with high sensitivity, photostability, and biocompatibility for fluorescence imaging. In particular, fluorescent probes with near‐infrared (NIR) emission (> 650 nm) have great potential due to their advantages of low photodamage to organisms, high signal‐to‐noise ratio, and deep tissue penetration.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…[ 9,12‐15 ] Notably, tumor‐derived EVs (or tumor EVs) are considered to be promising biomarkers in liquid biopsy owing to the strong correlation between the expression of membrane proteins and their host cells. [ 16‐21 ] In particular, previous studies revealed the presence of several tumor‐associated protein biomarkers in blood‐borne EVs, and their type and expression levels are linked to the presence and progression of specific cancer classes, including breast, [ 22 ] prostate, [ 23 ] and ovarian cancers. [ 24 ] However, up‐to‐date analysis of characteristic proteins on EVs still requires expensive antibodies, elaborate labeling, and detection procedures, which build significant barriers to clinical cancer diagnosis.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…Fluorescence probes could be excellent candidates as theranostic agents for anti-AD, due to the important merits of fluorescence in biomarker sensing, such as simple operation, high sensitivity, and availability in real-time tracking. 34 Notably, near-infrared (NIR) fluorescence, including the first NIR window (NIR-I, 650-900 nm) and the second NIR window (NIR-II, 1000-1700 nm), is suitable for in vivo bioimaging in imaging-guided theranostics, owing to its inherent advantages in minimizing tissue absorption, photon scattering, and autofluorescence. 35 To date, most of the AD theranostic agents have been derived from fluorescence probes of pathological factors.…”
Section: Fluorescence-guided Theranostic Agentsmentioning
confidence: 99%